Skeletal muscle metastasis from extrahepatic cholangiocarcinoma: A case report and literature review - Qian, Hongwei; Huang, Zhikun; Sun, Xuezheng; Ren, Peitu (Frontiers in Surgery, 2022)
Background: Cholangiocarcinoma (CCA) is a type of malignant tumor that arises from the epithelium of the bile ducts. According to anatomical location, CCA can be classified as intrahepatic (ICC), perihilar (PCC), or extrahepatic (ECC). CCA can invade and metastasize to other tissues in various ways, but distal skeletal muscle metastasis (SMM) is extremely rare. There are several reports on SMM from ICC or PCC, but SMM from ECC has not yet been reported. Case presentation: A 71-year-old woman was diagnosed with ECC, for which she underwent pancreatoduodenectomy and partial hepatectomy. Nine months after surgery, she was re-admitted to the hospital complaining of a rapidly growing mass on her right thigh with progressive lower extremity edema. Magnetic resonance imaging of the right thigh showed two masses with iso-signal intensity on T1-weighted images and hyper-intensity on T2-weighted images compared with the surrounding muscles. Pathological examination of the fine-needle biopsy specimen revealed that it was similar to the previously detected ECC, and the diagnosis was metastasis of ECC. The patient was treated with opioid analgesics and died of systemic failure three months later. Conclusion: SMM should be considered during the follow-up period despite its low incidence, and perineural invasion may be an essential pathway of distant metastasis in CCA.